Перспективы применения опалых листьев для целей локализации и сбора разливов нефтепродуктов - Сорока, Максим Леонидович; Ярышкина, Лариса Александровна (НПП ЧП «Технологический Центр», Харьков, 2013)
RU: Материалы статьи посвящены проблемам экологической безопасности перевозок нефтепродуктов на железнодорожном транспорте. В статье проанализирована целесообразность применения опалых листьев в качестве сорбентов для локализации и сбора разливов нефтепродуктов на железнодорожном транспорте. Экспериментально установлены эксплуатационные свойства сорбентов на основе опалых листьев и даны рекомендации по их целевому применению.

UK: Матеріали статті присвячені проблемам екологічної безпеки перевезень нафтопродуктів залізничним транспортом. У статті проаналізовано доцільність використання опалого листя в якості сорбентів для локалізації та збору розливів нафтопродуктів на залізничному транспорті. Експериментально встановлені експлуатаційні властивості сорбентів на основі опалого листя та надані рекомендації щодо їх цільового використання.

EN: This paper focuses on problems of the implementation of oil spill clean-up technology. This type technology is оften not effective because the sorbents are inaccessibly in the area of oil spill containment at the time. To solve the problem the authors propose the concept of using the waste of local industry as oil sorbent. The aim of this study is to highlight the possibility of using fallen leaves as a sorbent to clean-up the spill of oil and organic solvent. The laboratory experiments demonstrated that the sorbent based on fallen leaves showed good sorption properties and could be a viable alternative to traditional commercially synthetic sorbtion materials. Environment humidity is a limiting factor to the use efficiency of the fallen leaves. We concluded that the fallen leaves of trees should be used to create a local strategic sorbents reserve for the prompt organization of activities to clean-up oil spills.
Перспективи використання опалого листя з метою локалізації та збору розливів нафтопродуктів
The Prospects of Using Follen Leaves for the Clean-Up of Oil Spills
М. Сорока: ORCID 0000-0002-0558-6077
Keywords: сорбент; нефтепродукты; локализация; отходы; опалые листья; поглотительная способность; нафтопродукти; розлив; локалізації; відходи; опале листя; поглинальна здатність; oil; sorbent; spill; clean-up; waste; fallen leaves of trees; sorption capacity; organic solvent; КХІЕ